Angle steel energy dissipation self-resetting coupling beam section rotating around vertex and application thereof - GUO HONGCHAO; LIANG GANG; LI SHEN; FAN MIN; WANG ZHENSHAN (2024)
The invention discloses an angle steel energy dissipation self-resetting coupling beam section rotating around a vertex, which is connected between main structural beams of a required eccentric support steel frame and comprises a steel coupling beam section, a shape memory alloy rod and energy dissipation angle steel, the two ends of the steel coupling beam section are connected with a main structural beam of the eccentric supporting steel frame through energy dissipation angle steel, a shape memory alloy rod parallel to the steel coupling beam section is arranged in the steel coupling beam section and provides self-resetting tension, the shape memory alloy rod extends out of the end of the steel coupling beam section to be connected with the main structural beam, and long-strip-shaped holes are further formed in the end plate faces of the two ends of the coupling beam in the height direction of the coupling beam. The shape memory alloy rods penetrate through the long-strip-shaped holes and are prevented from